Preparation of natural polymer coating incorporating silver nanoparticles to extend shelf life of passion fruit - Nguyen, Ngoc Duy; Ho, Thi Bich Phuong; Le, Ho Minh Chau; Du, Dang Xuan (Hue University Journal of Science: Natural Science, 2025)
Passion fruit is highly perishable because of its vigorous metabolic activity after harvest. Therefore, "green" preservation using safe natural polysaccharides as functional coatings is of significant research interest. This study investigated the combined effects of chitosan and silver nanoparticle coatings at varying concentrations on the quality and shelf life of passion fruit. The results show that the appropriate chitosan concentration to prolong the preservation time was 1%. After 20 days of storage at 25 ± 2 °C, the weight loss was 19.59%. The total yeast and mold, soluble solids, acidity, and vitamin C content were 8.1 × 106 CFU/g, 14.5 °Bₓ, 6.31%, and 0.1583 mg/g, respectively. The coating from chitosan 1%-silver nanoparticles 5 mg/L solution was the most effective in the weight loss of the passion fruit at 17.4%, and the fruit peel colour changed insignificantly. The treated samples exhibited a total yeast and mold count of 1.3 × 10⁵ CFU/g, soluble solids of 14.83 °Bx, the acidity of 6.59%, and vitamin C content of 0.1841 mg/g. Interestingly, no silver nanoparticle residues were detected in the fruit flesh. These findings provided a scientific basis and demonstrated the practical potential of silver nanoparticle-chitosan coatings for effective fruit preservation.